Morphometrics and Meristics of Lemuru Fish Sardinella lemuru Bleeker, 1853 landed at TPI Aertembaga Bitung City - Rustandi, Yogi; Manginsela, Fransine; Bataragoa, Nego; Lumingas, Lawrence; Mandagi, Stephanus; Lohoo, Anneke V. (Sam Ratulangi University, 2023)
The morphometric and meristic study of the lemuru Sardinella lemuru landed at TPI Aertembaga, Bitung City aims to examine the ratio and proportion ratio between the total length and other morphometric parameters, the correlation index of growth patterns, the correlation index of closeness and correlation, determining the caudal fin ratio and determining its meristic character. The research was conducted in February-June 2023 and used a quantitative descriptive method. Of the 100 lemuru fish observed, there were 35 males with a total length between 13,184-15,589 cm and 65 females which were longer between 12,083-16,420 cm. The growth pattern of lemuru both male and female is positively allometric dominant with the lowest correlation index r (closeness) in the relationship of eye diameter to the total length of the male fish, namely r = 0.01 (very weak) and the highest in the standard length relationship to the total length of the female fish, namely r = 0.97 (very strong). The highest percentage ratio of other size parameters and total length was for the fork length of the male fish, which was 91.1% and the lowest was for the diameter of the female's eye, 4.2%. The tail fin aspect ratio of female fish is greater than male fish with a value of 1.61 for females and 1.57 for males. The meristics of the male lemuru are D 13-18, P 13-18, V 5-8, A 15-23 and C 17-25 and the females are D 13-18, P 12-18, V 6-9, A 13- 26 and C 15-28. Keywords: total length, small pelagic, growth status Abstrak Penelitian mengenai morfometrik dan meristik ikan lemuru Sardinella lemuru yang didaratkan di TPI Aertembaga Kota Bitung bertujuan untuk mengkaji rasio serta persentase rasio antara panjang total dan paramter morfometrik lainnya, indeks korelasi pola pertumbuhan, indeks keeratan hubungan korelasi dan, menentukan ratio sirip ekor serta menentukan karakter meristiknya. Penelitian dilaksanakan pada bulan Februari-Juni 2023 dan menggunakan metode deskriptif kuantitatif. Dari 100 individu ikan lemuru yang diamati ada 35 individu jantan dengan panjang total selang 13,184-15,589 cm dan 65 individu betina yang lebih panjang selang 12,083-16,420 cm. Pola pertumbuhan ikan lemuru baik jantan dan betina dominan allometrik positif dengan indeks korelasi r (keeratan) terendah pada hubungan diameter mata terhadap panjang total ikan jantan yakni r = 0,01 (sangat lemah) dan tertinggi pada hubungan panjang standar terhadap panjang total ikan betina yakni r = 0,97 (sangat kuat). Persentase rasio parameter ukuran lain dan panjang total tertinggi pada panjang garpu ikan jantan yakni 91,1 % dan terendah pada diameter mata betina 4,2 %. Aspek rasio sirip ekor lebih besar ikan betina daripada ikan jantan dengan nilai 1,61 pada betina dan 1,57 pada ikan jantan. Meristik ikan lemuru jantan yakni D 13-18, P 13-18, V 5-8, A 15-23 dan C 17-25 serta betina yakni D 13-18, P 12-18, V 6-9, A 13-26 dan C 15-28. Kata kunci: panjang total, pelagis kecil, status pertumbuhan